Pós-operatório pediátrico de fratura de antebraço: perfil e proposta de orientações - Rodrigues, Jéssica Barana (2018)
Delineate the profile of children submitted to surgical treatment from forearm fracture during the postoperative period, in order to analyze which variables directly or indirectly affect the procedure for correction; Identify the major complications during the postoperative period of children submitted to surgical treatment of forearm fracture to allow us to create a guide of guidelines according to the indicated need; Propose the design of guidelines for children undergoing surgical treatment of forearm fracture using Information and Communication Technologies, so that postoperative doubts and / or complications must be avoided. Methods: This is a cross-sectional study with descriptive design and a quantitative approach developed at the Orthopedic Trauma Center, in the city of São José do Rio Preto, São Paulo State. The study included all children aged from 0 to 11 year, who were victims of forearm fracture and underwent a surgical procedure for correction and concluded the treatment at the orthopedic trauma center, from February to May / 2018. Results: The results showed that 13 children were attended at the Orthopedic Center. The majority was males; the predominant fracture site was the left forearm with ages ranging from 7 to 8 years-old. The period with the highest incidence of events was evening, occurring exclusively with children above eight years. The activity performed occurred during leisure activities. At the time of occurrence, our results show that the children were mostly unaccompanied, with the most affected age ranging from seven to eight 8 years-old. All the events were related to leisure and physical activities. Conclusion: Forearm fractures in children, which occur mostly with unaccompanied boys, require special attention in the postoperative period. This can determine the success of the treatment or the occurrence of new unexpected factors An effective communication line, in the form of a Health Education strategy, is needed between children and those principally responsible for the success of treatment, such as a doctor, nurse, children and their families and / or caregivers. We propose the preparation of a guide of care related to the postoperative period of children submitted to surgical treatment of forearm fracture. We intend to design an application for Smartphones of easy access to all, in which information will be made available in a clear and objective way, with playful access containing information that children do not absorb at the time of discharge and other explanatory access, for family and caregivers receive complete guidelines and withdraw doubts online. Involving in this way, all in the appropriate treatment and consequent success of the consolidation of the fracture, reducing the incidence of intercurrences and future damages.